The borders of art - I. A. Bondarevska, (Ukrainian Cultural Studies, 2017)
The paper examines delimitation art and non-art as a crucial issue in contemporary philosophy of art. This thesis is developed with a special reference to Thierry de Duve’s nominalistic theory and is argued that this theory traces some opportunity for seeking answer the question indicated in the title. The author agrees with the main idea that name of an art is a performative, which makes changes in our mind and transform a mere thing into a work of art. This is an actual way to create the borders of art, which means to accept a unique point of view with a unique attitude to the world. The article states that the provocative statement "all can be art, but not all is art" gives us necessary tension to overcome the traditional essentialist mode of thinking. However, the author puts in question the ideas, which have implicit essentialist connotations. Duve’s theory argues that aesthetic judgement is a main condition for establishing the borders of art. The theory explores a crucial change of judgement about art. The judgment "this is art" is functioning like the judgment “this is beautiful” in the previous time and they two have equivalent attributes in the art and human life. I refute these ideas as not convincing and prove the alternative theses: the name of art performative power is determined primarily with social and cultural factors (not aesthetic judgment). The author offer the TV show episode The National Anthem (Black Mirror) as a model for testing the theory. It is evident that modern notion of art is tied to existence of the autonomous social "artworld" (Arthur Danto), or cultural field (Pierre Bourdieu) or social system (Niclas Luhmann). Any judgment about art cannot escape its destiny to divide people and social opinion. As a result, we have at least two subjects (instead of one) with different statuses and authority to say and to be heard. The author concludes that judgment “this is art” is political as such but judgment “this is beautiful” is not.
Keywords: Thierry de Duve, name of art, borders of art, art and non-art, system of art, art and policy, aesthetic judgment